Education and development for entrepreneurs in the canton of Atacames - Salazar Tuarez, Emma Angelina (Journal of business and entrepreneurial studie, 2022)
Accounting and tax education provides the necessary knowledge for the development of entrepreneurs. In this sense, this research was oriented to analyze the fulfillment of accounting and tax duties in order to describe the needs required to strengthen the tax education of entrepreneurs in the parish of Atacames canton. Methodologically it is a descriptive study, with an exploratory scope, using a sample of 296 entrepreneurs surveyed and a review of the tax regime for microenterprises. As a result of the characterization of the entrepreneurs, all of them are not registered with the Internal Revenue Service; the largest number of entrepreneurs have Ruc, they are not required to keep accounting records, the type of business is commercial, the time in operation is more than four years, they did not know about tax laws, they do not keep records of income and expenses, a few have workers in their business, a minimum number of workers are affiliated to social security. In conclusion, the entrepreneurs were interested in receiving training in accounting and tax issues, in addition to learning about tax regulations to comply with their tax obligations.